Time Course of Corticospinal Excitability and Autonomic Function Interplay during and Following Monopolar tDCS - Santarnecchi, Emiliano; Feurra, Matteo; Barneschi, Federico; Acampa, Maurizio; Bianco, Giovanni; Cioncoloni, David; Rossi, Alessandro; Rossi, Simone (Frontiers in Psychiatry, 2014)
While polarity-specific after-effects of monopolar transcranial direct current stimulation (tDCS) on cortico-spinal excitability are well-documented, modulation of vital parameters due to current spread through the brainstem is still a matter of debate, raising potential concerns about its use through the general public, as well as for neurorehabilitation purposes. We monitored online and after-effects of monopolar tDCS (primary motor cortex) in ten healthy subjects by adopting a neuronavigated transcranial magnetic stimulation (TMS)/tDCS combined protocol. Motor evoked potentials (MEPs) together with vital parameters (e.g. blood pressure, heart-rate variability and sympathovagal balance) were recorded and monitored before, during and after anodal, cathodal or sham tDCS. Ten MEPs every 2.5-minute time windows were recorded from the right First Dorsal Interosseus (FDI), while 5-minute epochs were used to record vital parameters. The protocol included 15 minutes of pre-tDCS and of online-tDCS, (anodal, cathodal or sham). After effects were recorded for 30 minutes. We showed a polarity-independent stabilization of cortical excitability level, a polarity-specific after-effects for cathodal and anodal stimulation, and an absence of persistent excitability changes during online stimulation. No significant effects on vital parameters emerged both during and after tDCS, while a linear increase in systolic/diastolic blood pressure and heart-rate variability was observed during each tDCS condition, as a possible unspecific response to experimental demands. Taken together, current findings provide new insights on the safety of monopolar tDCS, promoting its application both in research and clinical settings.